Perbedaan pengaruh metode inkuiri, motivasi belajar dan kompetensi matematika terhadap prestasi belajar fisika siswa sekolah menengah kejuruan negeri di Kabupaten Kebumen tahun 2013 - Akhmad Nuraeni (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to analyze: (1) whether there is difference influence between using learning Inquiry method with variatiaon speech method on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, (2) whether there is difference influence of student have high learning motivation with low learning motivation on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, (3) whether there is difference influence of student have high mathematic competence with low mathematic competence on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, and (4) how the learning interaction influence of learning method, learning motivation and mathematic competence on the Physics achievement of Senior Vocational High School students in the Kebumen regency. This research was conducted in Senior Vocational High School in the Kebumen regency academic year 2013/2014. The sampling technique used is multi-stage cluster random sampling. Engineering data collection using questionnaires and test techniques. Analysis using Analysis of Variance (ANOVA) Line 3. Based on the results of this study concluded : (1) there is difference influence between using learning Inquiry method with variatiaon speech method on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, (2) there is difference influence of student have high learning motivation with low learning motivation on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, (3) there is difference influence of student have high mathematic competence with low mathematic competence on the learning achievement of Physics Senior Vocational high school students in Kebumen Regency, and (4) there is interaction influence of learning method, learning motivation and mathematic competence on the Physics achievement of Â Senior Vocational High School students in the Kebumen regency.